Tanggungjawab Pendidik Perspektif Buya Hamka - Meyke Dita Cahyani; Shina Af'idatuz Zahwa (Pascasarjana Universitas Qomaruddin, 2024)
In general, Buya Hamka, a famous scholar and intellectual from Indonesia, often raises issues of education and the role of teachers in his works. He emphasized the importance of teachers' obligations to educate, guide and provide good examples to their students in aspects of religion, morals and knowledge. Hamka's works often promote the values of teachers who are responsible and care about the development of students' character. However, based on a general understanding of Buya Hamka's thinking, teachers' obligations are often emphasized in the context of holistic education, not only limited to transferring knowledge, but also guiding, educate morals, and shape students' character in accordance with religious and life values. Hamka may emphasize the importance of teachers' responsibilities as good role models in forming a quality generation.